BURNS UNIT : LISTENING AND A PSYCHOLOGIST ( RE ) CONSTRUCTION OF A PLOT FOR DIRECTIONS (Fiep Bulletin - online, 2015)
The subject affected by the burn is seen suddenly experiencing pain, hospitalization, and the commitment of its vital functions. Besides the process of depersonalization, the issue of pain, whether physical or emotional, is constant and follows the patient during hospitalization. To understand the contributions of the intervention of psychologist towards the patient with burns, in addition to addressing the implications of the patient's hospitalization and rehabilitation in the psyche of the individual affected by the burn. The method consists of an analysis of participant observation and field diary records produced during extracurricular internship at the Burns Unit of a public hospital, located in the state capital of Rio Grande do Sul. The results indicate that listening to the psychologist as an instrument intervention, is founded on the ability to provide a space for the patient to build and rebuild a sense of continuity. The establishment of a "piel de palabras", woven between the patient and a sympathetic interlocutor, can symbolically reestablish a continent psychic skin, able to make more tolerable the pain of a wound physical skin.
Keywords: Burn Unit; Health Psychology; Psychological adaptation.